Pengaruh Persepsi Risiko dan Kepercayaan (Trust) Terhadap Adopsi Layanan Fintech: Studi Kasus Pada Layanan Pembayaran Digital Dana Masyarakat di Desa Margajaya – Majalengka - Rufaidah, Fathi; Lestari, Indri; Trijumansyah, Andry (Techno Bahari, 2025)
Fintech, a term encompassing financial technology innovations, has introduced novel financial services, including digital payment platforms like the popular DANA e-wallet in Indonesia. However, the increasing number of risks associated with fintech has raised user concerns about its adoption. Despite these concerns, a significant number of users continue to adopt and utilize fintech services. To investigate the interplay between perceived risk, trust, and fintech adoption. Using a quantitative approach, the study employs descriptive-verificative analysis and multiple linear regression techniques to analyse the data. The findings reveal that perceived risk does not significantly impact fintech adoption in a negative direction. Conversely, trust exhibits a significant positive influence on fintech adoption. Additionally, the study establishes a significant joint influence of perceived risk and trust on fintech adoption.